INTELLIGENCE'S EFFECTS ON SECOND LANGUAGE LEARNING - M. Dian Yusuf Fikri (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2021)
It is often assumed that intellect is the most important element in determining whether or not a person would be successful in learning a second language. When compared to someone with a moderate IQ, someone with a high IQ learns a second language faster. However, this is not always the case. In my perspective, not every person with a high IQ finds it difficult to learn a second language. Other research discovered other factors that influence someone's performance in learning a second language. This demonstrates how various things impact someone's decision to learn a second language. The most significant variables in learning a second language are social variables. As a result, if they have medium intellect, learning a second language is not an issue. If they acquire a second language in a supportive atmosphere, they will be able to master the second language. As a result, selecting a decent social context in which to learn a second language is the most efficient approach to master it.